Antinuclear autoantibodies are more prevalent in COPD in association with low body mass index but not with smoking history. Issue 2 (3rd November 2010) - Bonarius, H P J; Brandsma, C A; Kerstjens, H A M; Koerts, J A; Kerkhof, M; Nizankowska-Mogilnicka, E; Roozendaal, C; Postma, D S; Timens, W
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is associated with a higher prevalence of antinuclear autoantibodies (ANAs). However, a significant subgroup of patients is ANA negative. It remains to be determined which patient groups carry autoantibodies. Methods: The association of smoking behaviour, disease status, gender, age and body mass index (BMI) with the presence of autoantibodies in the serum was determined in 124 patients with COPD and 108 non-COPD control subjects. In addition, the role of B cells in autoantibody generation in COPD was investigated by sequencing the antibody repertoire of B cells in the lungs of patients with COPD and of ex-smoking and never-smoking control subjects. Results: Patients with COPD had a significantly higher risk of being serum positive for ANAs (OR 3.12, 95% CI 1.68 to 5.76, p<0.001). ANAs were not significantly associated with age, smoking status, gender or pack-years of smoking. Within the COPD population, subjects with BMI <22 kg/m 2 had a significantly higher risk of ANAs (OR 4.93, 95% CI 1.50 to 16.50, p=0.009) than those with normal or high BMI. The antibody repertoire of B cells in the lungs of patients with COPD had a high frequency of positively charged CDR3 residues, a feature which is associated with self-reactive antibodies. Conclusion: The results show that COPD is a heterogeneous disease with respect to the prevalence of ANAs. ANAs are primarily associated with the presence of COPD and with low BMI, but not with smoking and forced expiratory volume in 1 s.